Gone girl: Richardson's ground squirrel offspring and neighbours are resilient to female removal. Issue 9 (4th September 2019) - Freeman, Angela R.; Wood, Thomas J.; Bairos-Novak, Kevin R.; Anderson, W. Gary; Hare, James F.
Abstract : Within matrilineal societies, the presence of mothers and female kin can greatly enhance survival and reproductive success owing to kin-biased alarm calling, cooperation in territory defence, protection from infanticidal conspecifics, joint care of young and enhanced access to resources. The removal of mothers by predators or disease is expected to increase the stress experienced by offspring via activation of their hypothalamic-pituitary-adrenal axis, increasing circulating glucocorticoids and reducing offspring survival and reproductive success. Yet, few studies have removed mothers in the post-weaning period to examine the assumed physiological and fitness consequences associated with these mortality events. We examined how the loss of a mother affects juvenile Richardson's ground squirrels' ( Urocitellus richardsonii ) faecal glucocorticoid metabolites and their survival. Given that neighbours are often close kin, we further hypothesized that conspecific removal would similarly diminish the fitness of neighbouring individuals. Upon removing the mother, we detected no impact on offspring or neighbouring conspecific faecal glucocorticoid metabolites in the removal year, or on overwinter survival in the following year. Furthermore, no impact on neighbour reproductive success was detected. Given the high predation rates of ground squirrels in wild populations, resilience to a changing social environment would prove adaptive for both surviving kin and non-kin.